Java after hours : 10 projects you'll never do at work - Holzner, Steven (Indianapolis, Indiana : Sams Publishing, 2006)
Containing ten projects, this book helps you learn to create graphics interactively on Web servers; send images to Web browsers; tinker with Java's Swing package to make it do seemingly impossible things; search websites and send e-mail from Java programs; and, use multithreading, Ant and more. Provides instructions for ten projects using Java, including developing image tools, constructing a chat room, creating an Internet intercom, and developing a weather forecaster.
1. Making fish swim in the multithreaded aquarium -- 2. Slapshot! : the interactive hockey game -- 3. graphicizer image-editing and conversion tool -- 4. Creating stunning graphics with painter -- 5. Chatting on the Internet with the Chat Room -- 6. Who's there? : logging access to your Website with WebLogger -- 7. Running any program via remote control with the robot -- 8. Creating a custom Web browser in Java : the browser project -- 9. Typing across the Internet : the intercom project -- 10. Getting a graphical weather forecast : the forecaster project.
Includes index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)